2014
DOI: 10.1038/srep03792
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in Toll-like receptors (TLRs 3/7/8) are associated with systemic lupus erythematosus in a Taiwanese population

Abstract: Toll-like receptors (TLRs), as innate immunity sensors, play critical roles in immune responses. Six SNPs of TLR3, TLR7, and TLR8 were genotyped to determine their associations with systemic lupus erythematosus (SLE) and clinical manifestations of SLE. TLR7 SNP rs3853839 was independently associated with SLE susceptibility in females (G vs. C: p = 0.0051). TLR7 rs3853839-G (G vs. C: p = 0.0100) and TLR8 rs3764880-G (recessive model: p = 0.0173; additive model: p = 0.0161) were associated with pericardial effus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 70 publications
2
72
2
3
Order By: Relevance
“…Hsin-Yi et al have shown that rs3775296, located in the 5′-UTR of TLR3, is associated with elevated TLR3 expression and susceptibility to knee osteoarthritis in a Chinese Han population [31]. Moreover, the rs3775296-T allele was associated with photosensitivity and anemia of system lupus erythematosus in females in a Taiwanese population [32]. However, in the present study, we failed to observe an association between rs3775296 and PE.…”
Section: Discussioncontrasting
confidence: 54%
“…Hsin-Yi et al have shown that rs3775296, located in the 5′-UTR of TLR3, is associated with elevated TLR3 expression and susceptibility to knee osteoarthritis in a Chinese Han population [31]. Moreover, the rs3775296-T allele was associated with photosensitivity and anemia of system lupus erythematosus in females in a Taiwanese population [32]. However, in the present study, we failed to observe an association between rs3775296 and PE.…”
Section: Discussioncontrasting
confidence: 54%
“…Nucleic acids are capable of activating a cohort of endosomal receptors, including but not limited to TRL7 and TLR9 (48,49), thus rendering these compounds partially effective in multifaceted autoimmune disorders that rely on multiple types of receptors. Moreover, TLR7 gene mutations play an important role in disease severity, and any therapies that directly target these receptors could potentially fail due to decreased mutant receptor binding (50)(51)(52). Our strategy does not rely on receptor binding, therefore, addressing a number of these concerns.…”
Section: Discussionmentioning
confidence: 99%
“…The Leu180 allele of MAL/TIRAP polymorphism indicated reduced susceptibility to SLE regarded as a protective factor against the development of SLE [60] . 12 The single nucleotide polymorphisms (SNPs) of TLR7 rs3853839, TLR8 rs3764880, together with TLR9 rs351240 have been shown to increase the risk of SLE in an Asian population [61,62].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…The single nucleotide polymorphisms (SNPs) of TLR7 rs3853839, TLR8 rs3764880, together with TLR9 rs351240 have been shown to increase the risk of SLE in an Asian population [61,62].…”
mentioning
confidence: 99%